PENGARUH GAYA KEPEMIMPINAN MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA PADA DINAS PEMBERDAYAAN MASYARAKAT DAN KAMPUNG DI KABUPATEN BERAU - Jubaidah, Winda (STIE Muhammadiyah Tanjung Redeb, 2018)
Leadership manner, motivation and work environment affect the performance of civil servant  at Department of Community and Village Empowerment in Berau Regency. Based on the results of the Hypothesis Test. It was shown that the  Test F  was found that Fcount with a value of 10.750> from Ftable with a value of 3.26 , Therefore, there was  a significant influence between the Independent variable (Y)  on the Dependent variable (Y). From the results of the t -test it was shown  that there was an influence between each independent variable on the dependent variable. Based on the Leadership manner variable, the value of  t-count was 2,291> from the value of T-table 2,02534, it can be seen that there was an influence between Variable X1 to Variable Y, then for motivation variable with t-count 2,313> from the value of t table 2,02534 it can be seen that there is an influence between variable X2 to variable Y, then the Work Environment variable with t-count 2.447> from the value of t table 2.02534 it can be seen that there is an influence between variables X3